Complication of Community-Acquired Pneumonia (Including Cardiac Complications) - Restrepo, Marcos I.; Reyes, Luis F.; Anzueto, Antonio (Seminars in Respiratory and Critical Care Medicine, 2016)
Community-acquired pneumonia (CAP) represents an important public health problem and carries significant morbidity, mortality, and costs. The incidence of CAP is highest among children and elderly patients, but the mortality is much higher in patients older than 65 years. Despite the advances in medicine, the administration of antimicrobials, and the overall better care, there are still patients with CAP dying due to systemic complications all over the world. A continuum of CAP disease progression may involve multiple organs beyond the pulmonary parenchyma. These pulmonary and nonpulmonary complications are associated not only with mortality but also with the development of clinical failure, prolonged hospitalization, and the need for more intensive level of care. In this review, we present the characteristics of several CAP-related pulmonary and nonpulmonary organ dysfunction, such as those affecting the heart, kidneys, hematological, neurological, endocrine systems. Multiple severity of illness scores identified a series of systemic findings that indicate the organ dysfunctions and the associated related outcomes. However, further research is required to address the mechanisms, the management, and prevention of organ dysfunction in patients with CAP.
Keywords: pneumonia; sepsis; complications; multiple organ dysfunction